Evaluation of Outcomes Following Endovenous Laser Therapy for Chronic Venous Insufficiency on a Daycare Basis in a Tertiary Healthcare Centre: A Prospective Cohort Study - Swati Pathak; Aditya Sharma; Rajeshwar Yadav (Nigerian Journal of Medicine)
Background: Chronic venous insufficiency (CVI) often presents with the development of incompetent short saphenous vein or great saphenous vein (GSV), resulting in a condition known as varicose veins. Materials and Methods: The present study was conducted with the aim of evaluating the outcomes and recurrence following endovenous laser therapy (EVLT) for CVI by discharging the patient on the same day following the procedure. Results: In this study, only 4 patients developed recurrence following varicose vein treatment out of 102 patients with EVLT on a daycare basis. An occlusion of GSV along with its branches was achieved in most of the cases with self-limiting adverse effects and very few recurrence rates in the follow-up period. Conclusions: Relief of symptoms and a significant improvement in the appearance of varicose veins were noted four–six months after initial treatment, and pain was greatly resolved in all the treated limbs.